1998
DOI: 10.1541/ieejfms1990.118.3_280
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conduction Mechanism of Carbon Black Polyethylene Composites Below the Percolation Threshold

Abstract: The electrical conduction mechanism of composites below the percolation threshold has been generally discussed with the hopping conduction model. In this article, the electrical conduction mechanism of carbon black-polyethylene composites below the percolation threshold is discussed based on the frequency dependence of conductivity in the range of 20 Hz to 1 MHz. There are two components for observed ac loss current. One is independent of frequency and becomes prevalent in low frequencies just below the percol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Resistivity of the fibers is assumed to be near to a percolation threshold at AB content 22%. Addition of a small amount of electro-conductive filler to materials in percolation threshold causes an extensive lowering in their resistivity [7,8]. In the present case, the water adsorbed is considered to play a role of an electro-conductive filler.…”
Section: Influence Of Draw Temperaturementioning
confidence: 89%
See 1 more Smart Citation
“…Resistivity of the fibers is assumed to be near to a percolation threshold at AB content 22%. Addition of a small amount of electro-conductive filler to materials in percolation threshold causes an extensive lowering in their resistivity [7,8]. In the present case, the water adsorbed is considered to play a role of an electro-conductive filler.…”
Section: Influence Of Draw Temperaturementioning
confidence: 89%
“…However, much stricter control of the electrical properties is required owing to growing demand for the picture with high resolution in electrophotography. Though some of the studies have been reported concerning the polymers filled with CB [6][7][8][9], there have been little work on the relation between variation of their average volume resistivity (AVR) depending on the surroundings where they are used and their processing conditions [10]. Under these circumstances, we have intended to develop electro-conductive fibers for a charging brush with excellent electrical properties which is applicable to color electrophotography.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that actual difference in surface resistivity is only about several times. The surface resistivity was measured under DC electric field, but results by Nakamura et al 12 indicate that resistance of semi-conductive materials is affected by percolation of carbon particles, and can vary with strength and frequency of electric field. Exploration of high-frequency response in a semi-conductive sheet (frequency response of surface resistivity) is needed for a more quantitative analysis.…”
Section: Simulation Of Pd Waveforms Using Equivalent Circuit Modelmentioning
confidence: 99%